2017
DOI: 10.1371/journal.pone.0186453
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between local peripapillary choroidal thickness and axial length, optic disc tilt, and papillo-macular position in young healthy eyes

Abstract: Optical coherence tomography (OCT) has made it possible for clinicians to measure the peripapillary choroidal thickness (ppCT) noninvasively in various ocular diseases. However, the ocular factors associated with the ppCT have not been conclusively determined. The purpose of this study was to determine the relationship between the local ppCT and the axial length, optic disc tilt, and the angle of the papillo-macular position (PMP) in healthy eyes. This was a prospective, observational cross-sectional study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(32 reference statements)
2
10
0
Order By: Relevance
“…In myopic eyes with axial lengths between 26 and 27 mm, pCT was thinnest at the temporal-inferior sector. Our finding agrees with those of previous reports 33,34 . Gupta et al .…”
Section: Discussionsupporting
confidence: 94%
“…In myopic eyes with axial lengths between 26 and 27 mm, pCT was thinnest at the temporal-inferior sector. Our finding agrees with those of previous reports 33,34 . Gupta et al .…”
Section: Discussionsupporting
confidence: 94%
“…A previous study has suggested that the degree of optic disc tilt may increase with the elongation of AL and the temporal side of the optic disc might be stretched; this deformation may happen in eyes with or without a posterior staphyloma. 29 Many other studies have reported a significant association between the presence of posterior staphyloma and choroidal thinning in highly myopic patients. [30][31][32] Although no obvious posterior staphyloma was found in the young myopia patients in the present study, subclinical staphylomas are sometimes observed in this population.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that axial length is significantly correlated with CT. Population‐based studies reported that myopic eyes had thinner subfoveal and peripapillary areas (Wei et al 2013; Jiang et al 2015), which were confirmed by other studies (Gupta et al 2015; Liu et al 2018; Duan et al 2019). Yamashita et al (2017) measured the peripapillary CT in eight sectors using a 3.4 mm circle scan and concluded that axial length showed a negative association with all circumferential sectors. In the present study, there was a significant negative correlation between axial length and several points of the CT, including the macular area (nasal 4, 5 and 6 and temporal 1, 2 and 3) and 2700 μm away from the nasal optic disc margin, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%